Implementation of Smart Contracts in Electronic Voting (Case Study: Election of the President and Vice President POLNES Student Executive Board) - Rahmat Wahyudi; Muhammad Farman Andrijasa; Noor Alam Hadiwijaya (JRST (Jurnal Riset Sains dan Teknologi), 2025)
The election of the candidates for President and Vice President of the Samarinda State Polytechnic Student Executive Board (BEM) still relies on conventional paper-based voting, which is susceptible to manipulation, ballot damage, and time-consuming vote counting. This research seeks to develop design and test for blockchain-based e-voting system prototype utilizing smart contracts to enhance efficiency, security, and transparency. Employing the Waterfall methodology, the research includes requirement analysis, system design using flowcharts and UML use case diagrams, smart contract implementation in Solidity on a local Ethereum network (Ganache), and testing via unit testing for smart contracts using Truffle and BlackBox testing for the user interface. Results demonstrate the system’s ability to automate the election process, including candidate and voter registration, identity verification via student ID, prevention of double voting, and real-time vote counting. Blockchain technology ensures immutability, transparency and guarantees data integrity. The results of this research can be an alternative solution that is more efficient, secure and transparent, by minimizing the risk of data manipulation, saving logistics costs, potential damage to voting media and accelerating the vote counting process which is automatically calculated by smart contracts. Overall, this system proves the potential of blockchain technology and smart contracts as a modern alternative to electronic voting systems.